Race and ethnicity in multi-ethnic schools : a critical case study - Ryan, James, 1952 October 18- (Language and education library, 1999)
"This book explores the representation of race/ethnicity in a multiethnic school. Employing a critical case study approach, it appeals to the wider social context to explain the unequal struggle over the meaning of race and ethnicity in the school. The book illustrates how representation and the discourses that make it possible are perpetually contested by students, parents and educators. In doing so it examines how the process of representation works through stereotyping, curriculum, identity and language practices to provide advantages for some and penalize others. The book also provides suggestions for how educators might find ways to introduce discourses that make it possible for traditionally marginalized students and members of the community to have their voices heard and to shape meanings that work in their interests."--Jacket